Effectiveness of QRIS as a Digital Instrument Innovation in Strengthening ZIS Fundraising A Study at the Muhammadiyah Zakat Institution (LAZISMU) of Makassar City - Muhammad Zul Ikram Safei; Nashrullah; Rahmawati Muin; Idris Parakkasi (LP2M IAIN Palopo, 2026)
This study aims to analyze the effectiveness of Quick Response Code Indonesian Standard (QRIS) as a digital innovation instrument in strengthening the collection of Zakat, Infaq, and Sadaqah (ZIS) funds at LAZISMU Makassar. This research employed a qualitative method with a phenomenological approach through interviews, observation, and documentation. The findings indicate that QRIS significantly improves the effectiveness of ZIS fundraising by providing faster transactions, operational efficiency, ease of access, and broader donor participation. QRIS also enhances transparency and accountability in zakat management through real-time digital transactions. However, several challenges remain, including limited digital literacy, inadequate technological infrastructure, and low public awareness regarding digital payment systems. To optimize QRIS utilization, LAZISMU Makassar implemented digital campaigns, institutional collaborations, and continuous public education programs. The study concludes that QRIS is an effective digital instrument for strengthening ZIS fundraising and supporting the transformation of modern Islamic philanthropy in the digital era..